KERAGAAN PERTUMBUHAN DAN HASIL EDAMAME (Glycine max (L.) Merr.), SERTA KESUBURAN TANAH PADA BERBAGAI DOSIS PUPUK KANDANG DAN LEGUME INOCULUM - Suwardike, Putu; Prabawa, Putu Shantiawan; Widyasaputra, Gede (Universitas Tribhuwana Tunggadewi, 2024)
Low organic carbon and soil nitrogen content is one of the factors limiting Edamame productivity. This research aimed to determine the dose of cow manure and legin that produces the best growth and yield of Edamame soybeans. The experiment was carried out in Sinabun Village, Sawan District using a complete factorial randomized block design, with two factors, namely the dose of cow manure and legin. The research showed that a single dose of cow manure had no significant effect on the growth performance, yield, and soil fertility of edamame soybeans. Treating legin at a dose of 7.5 g.kg-1 seed can increase plant height growth and pod weight per plant.